2021
DOI: 10.1177/16094069211053097
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Co-Creation: A Guide to Conducting Online Co-Creation Workshops

Abstract: COVID-19 has impacted research worldwide, with many researchers turning to online methods. While online and co-creation research methods are well established, there are no instructional articles or guides for researchers aiming to conduct online co-creation workshops. Such workshops can provide quality data and are increasingly used. This methods paper addresses this gap by outlining the steps involved in conducting online co-creation workshops. Using the TruSTFood sustainability food labelling study as an exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Second, the researchers decided to offer an incentive to the specialist trainees, because their registrations were very low. This strategy was also mentioned by former studies (Benson et al, 2021; Santhosh et al, 2021), which found this equally successful. Finally, in accordance with previous research, we recommend over-recruitment to counter the expected drop-out of 50% or more (Menary et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…Second, the researchers decided to offer an incentive to the specialist trainees, because their registrations were very low. This strategy was also mentioned by former studies (Benson et al, 2021; Santhosh et al, 2021), which found this equally successful. Finally, in accordance with previous research, we recommend over-recruitment to counter the expected drop-out of 50% or more (Menary et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…Most limitations identified in the current research were driven by the Covid pandemic outbreak and impacted the test of the OST procedure. The need to perform collaborative workshops in an online format raised a set of questions in relation to the process, which are in some cases aligned with participants' perceptions: not all participants were comfortable to use the technologies required; technical issues or lack of resources compromised the collaborative process; increased fatigue; lack of focus in the exercises due to other requests and commitments; adaptation to online platforms selected and use of more than one platform at the same time; online group discussion requires more facilitation and consequently a higher number of participants could have compromised the level of interaction with the performed tasks (Benson et al, 2021; Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The online setting has been found suitable to studies which focus on the generation of new ideas (see, e.g., Richard et al, 2021), and where collaborative and interactive processes between consumers are in focus (Bettiga et al, 2018). Also, online qualitative research has many recognised advantages including time and location flexibility, costeffectiveness, the potential for greater geographic reach and diversity of participants, and greater anonymity (Hesse-Biber and Griffin, 2013;Richard et al, 2020;Benson et al, 2021). However, the Covid-19 pandemic was also an influential factor, when deciding to carry out the workshops online.…”
Section: Methodsmentioning
confidence: 99%